Trauma Induced Coagulopathy - Gonzalez, Eduardo; Moore, Hunter B.; Moore, Ernest E. (Springer International Publishing : Imprint: Springer, 2016)
This text is aimed at defining the current concepts that define trauma induced coagulopathy by critically analyzing the most up-to-date studies from a clinical and basic science perspective. It will serve as a reference source for any clinician interested in reviewing the pathophysiology, diagnosis, and management of the coagulopathic trauma patient, and the data that supports it. By meticulously describing the methodology of most traditional as well as state of the art coagulation assays the reader will have full understanding of the tests that are used to study trauma induced coagulopathy. The evolving use of blood products as well as recently introduced hemostatic medications are reviewed in detail. Trauma Induced Coagulopathy will also be a valuable source for quick reference to the clinician that is faced with specific clinical challenges when managing coagulopathy.